An Existentialist Philosophical Perspective on the Ethics of ChatGPT Use - Andreas, Otto Mart; Samosir, Elisabet Marthawati (PT FORMOSA CENDEKIA GLOBAL, 2025)
The advancement of artificial intelligence (AI), particularly through ChatGPT, offers significant convenience but also raises ethical concerns related to autonomy, responsibility, and authenticity. This study critically examines AI usage through the lens of existentialist philosophy. Using qualitative methods and literature review, it explores the views of Jean-Paul Sartre, Martin Heidegger, and Søren Kierkegaard to analyze the ethical implications of AI for human existence. The findings suggest that AI use must align with personal freedom and responsibility. ChatGPT is not merely a tool but a medium that can shape human authenticity and may lead to existential alienation if uncritically used. Thus, ethical awareness and philosophical reflection are essential in navigating AI’s role in modern life.